Six Minutes Walking in Polio Survivors: Effects on Fatigue and Walking Adaptability - Jana Tuijtelaars; Max Keller; Frans Nollet; Merel-Anne Brehm; Jaap van Dieën; Melvyn Roerdink (Medical Journals Sweden, 2022)
Objective: To investigate whether 6-min walking is fatiguing for polio survivors, and how fatigue influences their normal and adaptive walking. Design: Cross-sectional study. Patients: Polio survivors (n = 23) with ≥ 1 fall and/or fear of falling reported in the previous year and healthy individuals (n = 11). Methods: Participants performed 1 normal-walk test and 2 walking-adaptability tests (target stepping and narrow-beam walking) on an instrumented treadmill at fixed self-selected speed, each test lasting 6 min. Leg-muscle fatigue (leg-muscle activation, measured with surface electromyography), cardiorespiratory fatigue (heart rate, rate of perceived exertion), gait and walking-adaptability performance were assessed. The study compared: (i) the first and last minute per test, (ii) normal and adaptive walking, and (iii) groups. Results: Leg-muscle activation did not change during normal walking (p > 0.546), but declined over time during adaptive walking, especially in polio survivors (p < 0.030). Cardiorespiratory fatigue increased during all tests (p < 0.001), especially in polio survivors (p < 0.01), and was higher during adaptive than normal walking (p < 0.007). Target-stepping performance declined in both groups (p = 0.007), while narrow-beam walking improved in healthy individuals (p < 0.001) and declined in polio survivors (p < 0.001). Conclusion: Cardiorespiratory fatigue might further degrade walking adaptability, especially among polio survivors during narrow-beam walking. This might increase the risk of falls among polio survivors. LAY ABSTRACT This study investigated whether prolonged walking is fatiguing for polio survivors and how this affects their ability to adapt walking to environmental circumstances (i.e. walking adaptability), which is an important skill for safe daily-life walking. A total of 23 polio survivors and 11 healthy individuals performed 1 normal-walk test and 2 walking-adaptability tests. To assess fatigue, leg-muscle activation, heart rate and rate of perceived exertion were measured. In addition, gait and walking-adaptability outcomes were assessed. The first and last minute per test, normal and adaptive walking, and groups were compared. Based on higher leg-muscle activation, heart rate and rate of perceived exertion, the study concluded that 6-min walking was more fatiguing for polio survivors than for healthy individuals and that adaptive walking was more fatiguing than normal walking, especially in polio survivors. Walking- induced fatigue further limits walking adaptability among polio survivors, which could increase their fall risk.